Construction of functional covalent organic framework films by modulator and solvent induced polymerization - Xuerong Li; Xingyue Ji; Xinglong Zhang; Xinyi Chen; Hongfeng Li; Suoying Zhang; Fengwei Huo; Weina Zhang (Nature Communications)
Abstract Covalent organic frameworks are attractive candidates for the next generation films in technical applications. However, due to their crystallization nature, insolubility in common solvents as well as infusible at high temperatures make it challenging to grow them spontaneously or process them into films. Herein, we report an efficient strategy to fabricate covalent organic framework films based on a modulator-solvent induced polymerization process. The addition of modulator slows down the nucleation rate during the initial stages of covalent organic framework growth, resulting in the formation of fluidic precursors that are easy to process. Subsequently, a suitable drying process is introduced to balance the evaporation rate of solvent and the crystallization rate of modulator induced, resulting in the formation of covalent organic framework films with a mixture of amorphous and crystalline structures. This strategy is universal for the fabrication of several types of covalent organic framework films with large-scale and freestanding state. Moreover, covalent organic framework films with asymmetric structure can function as organic vapor-triggered actuators, offering excellent repeatability and reversibility. By introducing functional molecules such as fluorescence, chirality and catalyst during the nucleation process, versatile functional covalent organic framework films can be easily fabricated, which endow them with broader application prospects.